Revisiting the Taxonomy of the Genus Arcobacter: Getting Order From the Chaos - Pérez-Cataluña, Alba; Salas-Massó, Nuria; Diéguez, Ana L.; Balboa, Sabela; Lema, Alberto; Romalde, Jesús L.; Figueras, Maria J. (Frontiers in Microbiology, 2018)
Since the description of the genus Arcobacter in 1991, a total of 27 species have been described, although some species have shown 16S rRNA similarities below 95%, which is the cut-off that usually separates species that belong to different genera. The objective of the present study was to reassess the taxonomy of the genus Arcobacter using information derived from the core genome (286 genes), a Multilocus Sequence Analysis (MLSA) with 13 housekeeping genes, as well as different genomic indexes like Average Nucleotide Identity (ANI), in silico DNA-DNA hybridization (isDDH), Average Aminoacid Identity (AAI), Percentage of Conserved Proteins (POCP) and Relative Synonymous Codon Usage (RSCU). The study included a total of 39 strains that represent all the 27 species included in the genus Arcobacter together with 13 strains that are potentially new species, and the analysis of 57 genomes. The different phylogenetic analyses showed that the Arcobacter species grouped into 4 clusters. In addition, A. lekithochrous and the candidatus species ‘A. aquaticus’ appeared, as did A. nitrofigilis, the type species of the genus, in separate branches. Furthermore, the genomic indices ANI and isDDH not only confirmed that all the species were well-defined, but also the coherence of the clusters. The AAI and POCP values showed intra-cluster ranges above the respective cut-off values of 60% and 50% described for species belonging to the same genus. Phenotypic analysis showed that certain test combinations could allow the differentiation of the four clusters and the three orphan species established by the phylogenetic and genomic analyses. The origin of the strains showed that each of the clusters embraced species recovered from a common or related environment. The results obtained enable the division of the current genus Arcobacter in at least seven different genera, for which the names Arcobacter, Aliiarcobacter gen. nov., Pseudoarcobacter gen. nov., Haloarcobacter gen. nov., Malacobacter gen. nov., Poseidonibacter gen. nov., and Candidate ‘Arcomarinus’ gen. nov. are proposed.